2021
DOI: 10.1029/2020jb020841
|View full text |Cite
|
Sign up to set email alerts
|

Lateral Seismic Anisotropy Variations Record Interaction Between Tibetan Mantle Flow and Plume‐Strengthened Yangtze Craton

Abstract: The southeastern Tibetan Plateau experienced intense Cenozoic shortening and extrusion along the western Yangtze Craton, SW China, where the Permian Emeishan flood basalts were emplaced. Seismic anisotropy along a dense E–W‐trending linear seismic array across the west Yunnan is determined by shear‐wave splitting analysis to characterize the deformation associated with these processes. Interestingly, a strong N–S‐oriented anisotropic zone collocated with the Eocene–Oligocene potassic magmatism is observed betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 75 publications
4
18
0
Order By: Relevance
“…The mafic crust composition of the INZ coincides with a region of high seismic wave velocity (Guo et al., 2017; T. Xu et al., 2015; Zhang et al., 2020), high density (Y. F. Deng et al., 2014), and high resistivity (X. Li et al., 2020). It is also consistent with the previous speculation that the INZ of the Emeishan LIP was significantly modified by the strong vertical deformation accompanied with magmatic emplacement (Chen et al., 2015; W. Li et al., 2021; Y.‐G. Xu & He, 2007).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The mafic crust composition of the INZ coincides with a region of high seismic wave velocity (Guo et al., 2017; T. Xu et al., 2015; Zhang et al., 2020), high density (Y. F. Deng et al., 2014), and high resistivity (X. Li et al., 2020). It is also consistent with the previous speculation that the INZ of the Emeishan LIP was significantly modified by the strong vertical deformation accompanied with magmatic emplacement (Chen et al., 2015; W. Li et al., 2021; Y.‐G. Xu & He, 2007).…”
Section: Discussionsupporting
confidence: 92%
“…Li et al, 2020). It is also consistent with the previous speculation that the INZ of the Emeishan LIP was significantly modified by the strong vertical deformation accompanied with magmatic emplacement (Chen et al, 2015;W. Li et al, 2021;.…”
Section: Discussionsupporting
confidence: 92%
“…There is an apparent low wave velocity anomaly in the crust and upper mantle below the CBM (Figure 3a). We argue that the upwelling of hot material from the deep mantle resulted in the change of the horizontal flow direction of the asthenosphere (Figure 4b) and thus induced the vertical seismic anisotropy that is undetectable for the steeply propagating SKS waves and would be ultimately featured as weak or nonsplittings (Li et al., 2021). Anisotropy investigation using over 20 years of seismic records showed that in this subduction region, a kind of convection flow associated with the BMW as deep as the MTZ might also contribute to the observed seismic anisotropy (Bi et al., 2020; G. R. Guo et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have employed receiver function, ambient noise tomography, and body‐wave and surface‐wave tomography methods to clarify both the Moho discontinuities and LAB near our study region (Wang et al., 2021; Wei et al., 2022; Zhou et al., 2012), with each of these studies suggesting a thin crust and thin lithosphere beneath Tengchong Volcano. A thick (150–180 km) lithosphere that underlies a crustal lid (35–50 km) has also been observed beneath the Sichuan Basin (Wang et al., 2018; Zhang et al., 2010, 2018), with the thick lithosphere beneath the basin being a typical characteristic of this ancient craton (Li et al., 2021; Wang et al., 2022).…”
Section: Distinct Lateral Variations Of Lithospheric Thickness In Sou...mentioning
confidence: 95%
“…Permian Emeishan flood basalts have been emplaced beneath the Chuandian region, with the lack of a detectable LAB aligning directly beneath the inner zones of the Permian Emeishan Large Igneous Province. The mantle plume model is a popular approach for explaining the geophysical and geochemical observations (Chen et al., 2015; Deng et al., 2016; Li et al., 2021; Xu et al., 2007) in large igneous provinces. The plume head could undergo strong changes and erode the overlying lithosphere owing to high temperatures and push it upward, with this being a common type of lithospheric thinning caused by a rising plume (Burov et al., 2007; Hawkesworth et al., 2017); this phenomenon is known as plume‐induced lithospheric destruction.…”
Section: Distinct Lateral Variations Of Lithospheric Thickness In Sou...mentioning
confidence: 99%